2012
DOI: 10.1051/0004-6361/201117919
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HCN, HCO+, and HNC in the Mrk 231 molecular outflow

Abstract: Aims. Our goal is to study gas properties in large-scale molecular outflows and winds from active galactic nuclei (AGNs) and starburst galaxies. Methods. We obtained high-resolution (1. 55 × 1. 28) observations of HCN, HCO + , HNC 1-0 and HC 3 N 10-9 of the ultraluminous galaxy (ULIRG) Mrk 231 with the IRAM Plateau de Bure Interferometer. Results. We detect luminous emission from HCN, HCO + and HNC 1-0 in the QSO ULIRG Mrk 231. All three lines show broad line wings -which are particularly prominent for HCN. Ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
261
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 209 publications
(287 citation statements)
references
References 40 publications
25
261
1
Order By: Relevance
“…If the receding OH is behind the source of 119 μm continuum emission, only ∼20% of that continuum within Δv = 500 km s −1 is thus intercepted and reemitted by the OH, indicating high clumpiness of the spatially extended reemitting OH. This is consistent with the clumpiness of the outflow inferred by Aalto et al (2012) from HCN emission. The ground-state OH79 doublet shows a relatively strong emission feature, with a flux that is nearly 75% of the absorption flux.…”
Section: Blueshifted Line Wings and The Oh65 Spectrumsupporting
confidence: 88%
See 1 more Smart Citation
“…If the receding OH is behind the source of 119 μm continuum emission, only ∼20% of that continuum within Δv = 500 km s −1 is thus intercepted and reemitted by the OH, indicating high clumpiness of the spatially extended reemitting OH. This is consistent with the clumpiness of the outflow inferred by Aalto et al (2012) from HCN emission. The ground-state OH79 doublet shows a relatively strong emission feature, with a flux that is nearly 75% of the absorption flux.…”
Section: Blueshifted Line Wings and The Oh65 Spectrumsupporting
confidence: 88%
“…We note, however, that this solution relies on our simple spherical geometry (where the successive shells are concentric) and may not be unique; for example, the high-and low-velocity gas may be flowing from different regions of a circumnuclear torus or disk, characterized by different T dust and possibly with different projection effects as the outflow widens. Nevertheless, some deceleration is most likely taking place because CO and HCN, which trace larger regions, show wings up to a velocity of ∼800 km s −1 from the line center (Feruglio et al 2010;Cicone et al 2012;Aalto et al 2012), significantly lower than OH. Spoon & Holt (2009) also inferred a decelerating velocity field from the ionized gas outflows traced by the [NeII], [NeIII] and [NeV] lines in a sample of ULIRGs, though not in Mrk 231; the fine-structure mid-IR lines trace an outflow on a significantly smaller spatial scale, however.…”
Section: Velocity Field?mentioning
confidence: 99%
“…The outflow phenomenon concerns virtually all the phases of the interstellar medium (ISM), including the ionized gas (e.g., Heckman et al 1990;Colina et al 1991;Martin 1998;Holt et al 2008;Crenshaw et al 2010;Rupke & Veilleux 2013;Arribas et al 2014), the neutral A&A 580, A35 (2015) atomic medium (e.g., Heckman et al 2000;Rupke et al 2002Rupke et al , 2005aRupke et al , 2005bRupke et al , 2005cMorganti et al 2005;Martin 2005Martin , 2006Chen et al 2010), as well as the molecular gas phase (e.g., Feruglio et al 2010;Fischer et al 2010;Sturm et al 2011;Alatalo et al 2011Alatalo et al , 2015Chung et al 2011;Aalto et al 2012;Dasyra & Combes 2012;Maiolino et al 2012;Combes et al 2013;Morganti et al 2013;Veilleux et al 2013;Cicone et al 2012Cicone et al , 2014Cicone et al , 2015García-Burillo et al 2014;González-Alfonso et al 2014;Davies et al 2014;Emonts et al 2014;Sakamoto et al 2014). This multiwavelength evidence underlines that the overall impact of outflows can only be quantified if all of their ISM phases are studied in different populations of galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent studies have also found massive outflows of molecular gas (Sakamoto et al 2010;Aalto et al 2012;Veilleux et al 2013), in particular, in Luminous Infrared Galaxies (LIRGS) and Ultra Luminous Infrared Galaxies (ULIRGS).…”
Section: Introductionmentioning
confidence: 99%